Effect of different times and methods of nitrogen appllication on, maize yieid, quantity of protein, efficienc of the fertilizer and its conversion in protein, utilizing ammonium sulphate-15N - Neptune, André Martin Louis (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
The experiment herein described was carried out in a podzolic soil, in the State of São Paulo, Brazil, with the double hybrid corn HD-6999 B. The folowing conlclusion can be drawn: 1) In respect the placement and times of nitrogen fertilizer application, the data showed there was no significant difference among the methods of application, although the plots which received the nitrogen a) in banding, b) in banding plus sidedressing or c) in plowrig down plus sidedressing, gave better yields. (7.100 kg/ha). These data were corroborated by the per cent uptake of nitrogen in the plant derived from the fertilizer. 2) Sidedressing nitrogen, 40 days after sowing, gave the higher quantity of protein (377 Kg/ha) coming from the fertilizer and the higher efficiency of the nitrogen fertilizer in its conversion in protein (60%). 3) Good correlation (r = 0.691) has been found between corn yield and concentration of nitrogen in the leaf chose for diagnostic purpose of the N status of the corn plant.